Miswak users’ behavior model based on the theory of planned behavior in the country with the largest Muslim population - Bramantoro T; Karimah N; Sosiawan A; Setijanto RD; Berniyanti T; Palupi R; Wening GRS (Dove Medical Press, 2018)
Taufan Bramantoro,1 Navilah Karimah,2 Agung Sosiawan,1 Raden Darmawan Setijanto,1 Titiek Berniyanti,1 Retno Palupi,1 Gilang Rasuna Sabdho Wening1 1Department of Dental Public Health, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia; 2Dental Medicine Program, Faculty of Dental Medicine, Universitas Airlangga, Surabaya, Indonesia Background: Maintaining proper oral hygiene has an influence on oral health. Religious obedience may influence individual behavior. According to Islamic religious guidance, as recommended by an Islamic role model, it is obligated to maintain oral health and the recommended tool to use is miswak. Purpose: To describe miswak users’ behavior based on the theory of planned behavior. Subjects and methods: The population of this study was the students of As-Salafi Al-Fitrah Islamic Boarding School who used miswak regularly and were healthy physically and mentally. One hundred and nine samples were chosen randomly and asked to complete a semi-open and a closed-ended questionnaire. Results: Perceived behavioral control had the most dominant influence toward improving intention with β=0.211 and p<0.05. In contrast, attitude and subjective norms had less influence toward improving intention with β=0.190 and p>0.05, and β=0.164 and p<0.0001, respectively. Meanwhile, perceived behavioral control showed direct correlation toward action in model parameter with β=0.445 and p<0.0001. Conclusion: Perceived behavioral control is the most dominant predisposing factor in increasing intention and attitude of miswak use. Keywords: attitude, subjective norm, perceived behavioral control, intention, miswak use